Developing Ekasari as a Sustainable Tourism Village - Ernawati, Ni Made; Sanjiwani, I Gusti Agung Mirah; Arjana, I Wayan Basi; Mudana, I Gede (Bali Membangun Bali: Jurnal Bappeda Litbang, 2024)
Purpose: Ekasari Tourism Village in Melaya District, Jembrana Regency, has potential to conduct sustainable tourism. This research is to increase public understanding about sustainable tourism, to improve the ability of village managers in implementing a financial recording system, and to increase the application of digital marketing to managers of the Ekasari Tourism Village. Research methods: This qualitative research is an applied research, with data collection techniques in the form of participant-observation, interviews, and document study. The data found was then analyzed using interactive techniques consisting of data reduction, presentation, and conclusion. Results and discussion: The service activities and this research went well, marked by an increase in participants' understanding of the importance of sustainable tourism in the village as well as an increase in digital marketing skills and the use of financial recording systems. Implication: This research directly has a positive impact on participants, especially village managers and Pokdarwis in operational activities and efforts to develop the village towards a sustainable tourism village.